Barriers Faced by Adolescents in Pursuing Higher Education in Komba Village, Luwu Regency - Rahmawati, Rahmawati; Karadona, Rosika Indri; Alamsyah, Muhammad Nur (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to explore the factors that hinder adolescents from pursuing higher education in Komba Village, Luwu Regency. Employing a qualitative approach with a phenomenological method, the research delves into the subjective experiences of adolescents, parents, and local community leaders through interviews, observations, and documentation. The findings reveal that the barriers faced by adolescents stem from both internal and external factors. Internal factors include low motivation and interest in continuing education, the desire for economic independence, and cultural influences such as early marriage. External factors involve the limited role of parents, an unsupportive social environment, and constrained family economic conditions. Moreover, prevailing societal views that higher education does not guarantee a better future further reinforce these barriers. This study recommends the adoption of a holistic and community-based approach through education, strengthening the roles of families and community leaders, and providing scholarship programs to encourage adolescents to pursue higher education.